Design, simulation, and validation of additively manufactured high-temperature combustion chambers for micro gas turbines. (15th November 2021) - Adamou, Adamos; Turner, James; Costall, Aaron; Jones, Andy; Copeland, Colin
Highlights: Micro gas turbines exhibit poor efficiency and emissions due to their small scale. Additive manufacturing enables novel combustor design features to reduce emissions. A validated computational flamelet combustion model is used to design new features. Six additively manufactured swirler, injector, mixing features are combustor tested. Mixture quality improves 20%, nitrogen oxides reduce by 75%, carbon monoxide by 40%. Abstract: The demand for cleaner, more efficient, and durable sources of electricity is driving research into small-scale power generation. Micro gas turbines are especially suitable by virtue of their high power density and reliability, but a major drawback is their poor overall efficiency due to increasing parasitic energy losses relative to net power output as size decreases. Additive manufacturing offers design freedoms that could enable higher efficiency and lower emission combustors for micro gas turbine applications. A novel conical radial swirl-stabilized tubular combustor with internal vane fuel injection is designed and tested, and a validated reacting computational fluid dynamics model is used to design novel combustor features that can only be additively manufactured. Of the five different concepts tested, those benefitting from additively manufactured features outperform the traditional design in terms of peak temperature control and fuel–air mixing, translating to striking reductions in pollutant emissions, with up to 75% and 40% reductions in nitrogen oxides and carbon monoxides, respectively, while concepts incorporating upstream fuelling and a three-row lattice show a near 20% increase in mixture quality. As well as evaluating a number of novel and very promising additively manufactured combustor design features, this work provides guidance on the incorporation of additively manufactured features in combustors for any gas turbine application and demonstrates the clear benefits of additive manufacturing for low-emission combustor design.